The effect of static versus dynamic depictions of actions in verb and sentence production in aphasia. Issue 10 (3rd October 2017) - Blankestijn-Wilmsen, Joyce; Damen, Ilona; Voorbraak-Timmerman, Vicky; Hurkmans, Joost; Brouwer de Koning, Janneke; Pross, Anne; Jonkers, Roel
ABSTRACT: Background : There is a shortage of material for the treatment of verb and sentence production in persons with aphasia (PWAs). In therapy, pictures or photographs depicting actions are often used, even though the meaning of certain verbs clearly involves movement. This aspect of movement is difficult to depict on static material. In a case study, Druks, J., & Shallice, T. (2000). Selective preservation of naming from description and the "Restricted Preverbal Message". Brain and Language, 72, 100–128. doi:10.1006/brln.1999.2165 reported a patient who had difficulties naming actions. However, when the actions were performed, the patient was better at naming performed actions compared to naming actions depicted in still pictures. Aims : In the current study, we tested the hypothesis that PWAs are more accurate in naming verbs in isolation as well as in sentence context in a dynamic condition rather than in a static condition. In a second experiment, we examined whether the use of verbs that express specific types of movement has any influence on the production of verbs when using static and dynamic depiction. Verbs in three semantic categories were included, namely action verbs relating to arm, leg and face movements. Methods & Procedures : In the first experiment, verb production was examined in a static (photographs) condition and a dynamic (videos) condition. An action-naming task and a sentence production task of 20 items each were administered to 18 PWAs. In the second experiment, an action-naming task of 60 items was administered to 13 PWAs. Outcomes & Results : PWAs scored significantly better in the dynamic condition compared to the static condition on both the action-naming task and the sentence-production task in Experiment 1. Considering the three semantic categories that were considered in Experiment 2, PWAs only scored significantly better on the category "arm" in the dynamic condition as compared to the static condition. Conclusions : These results suggest that semantic information of an action's specific aspects, such as movement, is activated while watching an action. We assume that PWAs profit from this depiction of movement. This study implicates that in clinical practice, dynamic material, rather than static material, should be used in diagnosis and therapy involving action naming and sentence production.